2022
DOI: 10.1186/s12882-022-02848-x
|View full text |Cite
|
Sign up to set email alerts
|

The rate, cost and outcomes of parathyroidectomy in the united states dialysis population from 2016–2018

Abstract: Background In end-stage kidney disease, patients may undergo parathyroidectomy if secondary hyperparathyroidism cannot be managed medically. This study was designed to estimate the parathyroidectomy rate in the United States (US) and to quantify changes in costs and other outcomes after parathyroidectomy. Methods This was a retrospective observational cohort study using US Renal Data System data for 2015–2018. Parathyroidectomy rates were estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Nevertheless, the rate of parathyroidectomy in the United States decreased to ~7 per 1000 dialysis patient‐years between 2002 and 2011, regardless of an increase in mean blood parathyroid hormone concentrations, suggesting the introduction of calcimimetics and uncertainty concerning ideal parathyroid hormone targets 2 . The parathyroidectomy rate decreased further from 6.5 per 1000 person‐years in 2016 to 5.3 per 1000 person‐years in 2018 3 . Moreover, parathyroid surgery should not be too radical, particularly if the patient is a candidate for a future kidney transplantation 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the rate of parathyroidectomy in the United States decreased to ~7 per 1000 dialysis patient‐years between 2002 and 2011, regardless of an increase in mean blood parathyroid hormone concentrations, suggesting the introduction of calcimimetics and uncertainty concerning ideal parathyroid hormone targets 2 . The parathyroidectomy rate decreased further from 6.5 per 1000 person‐years in 2016 to 5.3 per 1000 person‐years in 2018 3 . Moreover, parathyroid surgery should not be too radical, particularly if the patient is a candidate for a future kidney transplantation 4 …”
Section: Introductionmentioning
confidence: 99%
“…2 The parathyroidectomy rate decreased further from 6.5 per 1000 person-years in 2016 to 5.3 per 1000 personyears in 2018. 3 Moreover, parathyroid surgery should not be too radical, particularly if the patient is a candidate for a future kidney transplantation. 4 One of the complications of parathyroidectomy is hungry bone syndrome due to hyperdynamic calcium reabsorption into bones following parathyroidectomy, with an acute drop in parathyroid hormone concentration.…”
Section: Introductionmentioning
confidence: 99%
“…This risk is similar to those taking cinacalcet (18% incidence of calcium <1.87 mmol/L) or who receive a parathyroidectomy for secondary hyperparathyroidism (31% incidence of calcium <1.87 mmol/L), both of which are strategies used to decrease fracture risk in individuals receiving dialysis. (38)(39)(40)(41) To our knowledge, this is the largest cohort study of new denosumab users focused upon the risk of hypocalcemia after drug administration. Denosumab use has been increasing over the last 10 years, including in populations not studied in the original efficacy trials (ie, those with CKD).…”
Section: Discussionmentioning
confidence: 99%
“…This risk is similar to those taking cinacalcet (18% incidence of calcium <1.87 mmol/L) or who receive a parathyroidectomy for secondary hyperparathyroidism (31% incidence of calcium <1.87 mmol/L), both of which are strategies used to decrease fracture risk in individuals receiving dialysis. ( 38‐41 )…”
Section: Discussionmentioning
confidence: 99%
“…3 Indeed, for parathyroidectomy, one study reported that at the end of the first postsurgical year, up to 39% of patients still had hypocalcemia (<8.5 mg/dL) and total mortality was 3.5%. 2 Antifracture strategies in dialysis patients must go beyond a sole focus on parathyroid hormone reduction. Bone strength is dependent on the quality of bone.…”
mentioning
confidence: 99%